The Study of Interaction of Melphalan with SWCNT- BNNT Through Force Fields Molecular Mechanics and Quantum Calculations in Different Solvents and Temperatures - Jamshidi, Mohammad H.; Hasanzadeh, Neda; Yahyaei, Hooriye; Bahrami, Amir (Letters in Organic Chemistry, 2023)
In this study, the interaction of Melphalan, which is an anti-cancer medicine, with Singlewall carbon nanotubes (SWCNTs) and Boron nitride nanotubes (BNNTs), was investigated. Calculations were performed by using two methods of quantum mechanics and molecular mechanics. Thermodynamic parameters and Frontier Molecular Orbitals (FMOs) of the title compounds were evaluated by using the Density Functional Theory (DFT) calculations. The Quantum Mechanics calculations proved that BNNTs are more suitable carriers for Melphalan. Moreover, the interaction of Melphalan with SWCNTs and BNNTs at different temperatures was evaluated by Monte Carlo calculations. The MM+ force field was chosen as the most efficient field, and the HCl solvent has the lowest amount of energy and proven to be the most stable solvent for the simulation. The most significant finding obtained from this study is that the results of all types of calculations are in line with each other regarding both thermodynamic properties and conformers.
Keywords: Melphalan